Respon pertumbuhan stek pucuk jambu madu ( Syzygium aquaeum ) pada media Tanam dan lama perendaman air Kelapa Muda - Beno Enggelika; Dermawan Hutagaol; Nurma Ani (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
Customers venerate the commercial fruit plant known as Guava Madu Deli Hijau, which provides superior benefits to guava in general. This research seeks to determine the influence of growing medium, immersion time in young coconut water, and their interactions on the development of Syzygium aqueum stalk cuttings. The investigation was conducted between March and June of 2023. This study used a factorial randomized block design with two examined variables and three iterations. The first component was the availability of planting media (M), which came in four levels: sand, peat moss, vermiculite, and soil M0 = control, M1 = soil + cocopeat, M2 = soil + compost, M3 = soil + burnt husks. The second factor was the soaking time of the shoot cuttings in young coconut water (A) which consisted of 3 levels, namely A0 = control, A1 = 90 minutes, A2 = 180 minutes. The results showed that the growing medium treatment had no influence on the proportion of surviving cuttings but had a substantial effect on plant height, number of leaves, number of branches, root volume, and root length. The amount of time spent immersed in young coconut water had an effect on the number of leaves, seedlings, root volume, and root length, but not on the proportion of cuts that developed or plant height. The interaction between different planting media and the period of immersion in juvenile coconut water had no influence on any of the characteristics measured.